THE PHYLOGENETIC POSITION OF THE PAPUASIAN GENUS SARCOCHILUS R.BR. (ORCHIDACEAE: AERIDINAE): EVIDENCE FROM MOLECULAR DATA - Topik - Hidayat; Motomi - Ito; Tomohisa - Yukawa (Reinwardtia, 2008)
HIDAYAT,T.; ITO, M.; YUKAWA, T. 2008. The phylogenetic position of thePapuasian genus Sarcochilus R.Br.(Orchidaceae: Aeridinae): evidence from molecular data. Reinwardtia 12(4).281 – 284. –– The taxonomic status of the Papuasian orchid genus Sarcochilus R.Br. remains unresolved. Represented by Sarcochilus chrysanthus Schltr.,a phylogenetic analysis to evaluate relationships between the Papuasian species and those from Australia was conducted using molecular characters.Parsimony analysis using DNA sequences of the internal transcribed spacer (ITS) region showed that this Papuasian species, is in a distant position from the so-called the true Sarcochilus sensu stricto.These results provide additional evidence for the establishment of a new genus Monantochilus.